Mobile Web Based Mini Games for Locatify - Jón Rúnar Helgason 1986-; Eric Jon Nielsen 1989-; Þórður Hermannsson 1987- (2013)
Final report. A printed copy and all related data can be found on an accompanying CD hosted by the library at Reykjavík University. Heildartexti lokaskýrslu. Prentuð útgáfa og öll fylgiskjöl á CD eru varðveitt í bókasafni HR. This document is a final report for the final project Mobile Web Based Mini Games for Locatify. The project was done in the course T-404-LOKA from Reykjavík University in order to qualify for a BSc degree in Computer Science. In this course companies submitted project proposals that students then chose to work on for one semester or 15 weeks. Our final project was to design standalone mini games for the privately held company Locatify using the mobile framework PhoneGap as well as HTML5, CSS, and JavaScript.